2019
DOI: 10.18517/ijaseit.9.3.2943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laminate Arrangement on the Failure Behaviour of Hybrid Composite Plates under Transverse Sinusoidal Load

Abstract: The present work deals with the effects of laminate arrangement on the failure behaviour of hybrid composite plates under transverse sinusoidal load. Failure analysis has been a subject under study for many years, especially for composite materials. This is largely due to the spontaneous nature of composite materials when it fails without warning. Hybrid composite are commonly utilized to improve the unexpected and instantaneous failure mode of composites. Nevertheless, the failure behaviour of hybrid composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Keshavamurthy et al 11 designed and analyzed a hybrid composite spring composed of E-glass/epoxy and carbon/epoxy using ANSYS. Ghani et al 12 studied the effects of laminate arrangement on the failure behaviour of hybrid composite plates under transverse sinusoidal load. Modeling and analysis have been done in ANSYS using maximum stress criteria, Ghani et al 12 showed the strength variation of hybrid composite plates with different lamination arrangements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keshavamurthy et al 11 designed and analyzed a hybrid composite spring composed of E-glass/epoxy and carbon/epoxy using ANSYS. Ghani et al 12 studied the effects of laminate arrangement on the failure behaviour of hybrid composite plates under transverse sinusoidal load. Modeling and analysis have been done in ANSYS using maximum stress criteria, Ghani et al 12 showed the strength variation of hybrid composite plates with different lamination arrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Ghani et al 12 studied the effects of laminate arrangement on the failure behaviour of hybrid composite plates under transverse sinusoidal load. Modeling and analysis have been done in ANSYS using maximum stress criteria, Ghani et al 12 showed the strength variation of hybrid composite plates with different lamination arrangements. Furthermore, numerous experimental works have been conducted to study the effect of hybridization on tensile strength, impact strength and the effective properties of the composite.…”
Section: Introductionmentioning
confidence: 99%